2019
DOI: 10.21577/0103-5053.20190075
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Non-Ionic Pathway for Uncatalyzed Prins Cyclization: DFT Approach

Abstract: Density functional theory calculations (ωB97X-D/6-311++G(d,p)) are employed to investigate an alternative pathway for Prins-like cyclization. Although strong acids usually catalyze this reaction, 4-amino-1,3-dioxanes are rapidly obtained in high yields without catalyst when benzenamines and acetaldehyde react at low temperatures, in aqueous medium. Considering these conditions, we applied a supermolecule model with explicit water molecules to compute the mechanism for 4-amino-1,3-dioxanes formation from the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 36 publications
(46 reference statements)
0
7
0
Order By: Relevance
“…The solvent arrangement around the solute can be obtained by a top-down approach starting with a condensed phase simulation (using molecular dynamics or Monte Carlo calculations), and only a few explicit solvent molecules are selected for a DFT level evaluation. 23,26,63,64 Herein, we combine both models, known as the hybrid cluster-continuum model, to simulate solvent effects (DMSO and H 2 O) on the rotational isomerism. We chose the simulated solvent compatible to experimental available data.…”
Section: Rotational Isomerism: the Substituent Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The solvent arrangement around the solute can be obtained by a top-down approach starting with a condensed phase simulation (using molecular dynamics or Monte Carlo calculations), and only a few explicit solvent molecules are selected for a DFT level evaluation. 23,26,63,64 Herein, we combine both models, known as the hybrid cluster-continuum model, to simulate solvent effects (DMSO and H 2 O) on the rotational isomerism. We chose the simulated solvent compatible to experimental available data.…”
Section: Rotational Isomerism: the Substituent Effectsmentioning
confidence: 99%
“…Computational evaluations have indicated that incorporating explicit solventsolute interactions in simulations can result in distinct chemical phenomena, including changes in reactivity, types of reaction mechanisms, and isomerism. [23][24][25] Herein, we employed for the first time Density Functional Theory (B3LYP-D3/6-311++G(d,p)) to investigate how the substituents and the solvent affect the rotational isomerism in C-glycosyl flavonoids. This quantum method can access the transition state of bond rotation and dispersive interactions along the flavonoid backbone that can influence the isomerism.…”
Section: Introductionmentioning
confidence: 99%
“…, 3–4 Å) or based to the radial pair distribution function, to be evaluated at the quantum level. 4,17–20 In the bottom-up approach, explicit solvent molecules are added one by one around the substrate, seeking stable interactions based on the user's chemical intuition or molecular electrostatic potential analysis. 16,21–25…”
Section: Introductionmentioning
confidence: 99%
“…20 In both cases, the authors determined the number of water molecules based on the radial pair distribution function. 19,20…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation